Assessing the status of biological control as a management tool for suppression of invasive alien plants in South Africa - Zachariades, Costas; Paterson, Iain D.; Strathie, Lorraine W.; Hill, Martin P.; van Wilgen , Brian W. (African Biodiversity & Conservation, 2017)
Background: Biological control of invasive alien plants (IAPs) using introduced natural enemies contributes significantly to sustained, cost-effective management of natural resources in South Africa. The status of, and prospects for, biological control is therefore integral to National Status Reports (NSRs) on Biological Invasions, the first of which is due in 2017.Objectives: Our aim was to evaluate the status of, and prospects for, biological control of IAPs in South Africa. We discuss expansion of biological control and suggest indicators to be used in the upcoming NSR to assess sufficient growth.Method: We used published literature, unpublished work and personal communication to assess the status of biological control of IAPs. We propose indicators based on the targets for biological control that were proposed in the 2014 ‘National Strategy for dealing with biological invasions in South Africa’. To prioritise targets for future efforts, we used published lists of damaging IAPs and assessed the prospects for their biological control. Recommendations for using biological control as a management tool were made after discussion among the authors and with colleagues.Results: Significant control of several Cactaceae, Australian Acacia species and floating aquatic plants, and many other IAPs has been achieved in South Africa since 1913. Recently, biological control has benefited from improved international collaboration, a streamlined application process for the release of new biological control agents (resulting in the approval of 19 agents against 13 IAP species since 2013), and increased funding and capacity. There is still a needto improve implementation and to better integrate biological control with other control methods. In order to maximise benefits from biological control, increased investment is required, particularly in implementation and post-release evaluation, and in targeting new IAPs. Proposed targets for growth between 2017 and 2020 include an increase in financial investment in research by 29%, implementation by 28% and mass-rearing by 68%. Research capacity should increase by 29%, implementation capacity by 63% and mass-rearing capacity by 61%. New research projects should be initiated on 12 new IAP targets, while post-release monitoring efforts should be expanded to another 31 IAPs.Conclusion: Biological control of IAPs has contributed substantially to their management in South Africa, and continues to do so. Further investment in targeted aspects of IAP biological control will increase this contribution.